DISCOURSE ANALYSIS IN THE PERSPECTIVE OF ERNESTO LACLAU AND CHANTAL MOUFFE - Narwaya, St Tri Guntur (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
This article elaborates on the discourse analysis approach developed by Ernesto Laclau and Chantal Mouffe. Laclau and Mouffe's ideas are still relatively new in the realm of communication studies in Indonesia. These two thinkers are more familiar with various contemporary political studies literature. Much of their theoretical arguments refer to the Neo-Marxist framework as well as the Post-structuralist perspective. This article provides the fundamental concepts developed by Laclau and Mouffe in assisting the broader socio-political discourse analysis. Laclau and Mouffe reject various basic assumptions from essentialism, foundationalism, discursive representationalism, and deconstructive approach. Using a critical literature review method, we examine the thoughts of Laclau and Mouffe in developing the discourse studies. Laclau and Mouffe's approach is practical for multiple communication studies such as political discourses, business communication, branding discourses, news analysis, and other social communication themes. It can be used to explore and study how, for example, a hegemonic discourse articulated in the practice of certain political discursive formation by various dominant political forces. Also, it is able to capture how a certain discursive topic negotiated and contested by various existing socio-political power. The implication can also extend to broader issues related to discursive practices because for Laclau and Mouffe, every social practice can be read from the lens of a discourse. To cite this article (7th APA style):Narwaya, S. T. G. (2021). Discourse Analysis in the Perspective of  Ernesto Laclau and Chantal Mouffe. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(1), 1-11. http://dx.doi.org/10.36782/jcs.v1i1.2106